ICARUSS, the Integrated Care for the Reduction of Secondary Stroke Trial: Rationale and Design of a Randomized Controlled Trial of a Multimodal Intervention to Prevent Recurrent Stroke in Patients with a Recent Cerebrovascular Event, ACTRN = 12611000264987. Issue 5 (July 2015) - Joubert, J.; Davis, S. M.; Hankey, G. J.; Levi, C.; Olver, J.; Gonzales, G.; Donnan, G. A.
Background: The majority of strokes, both ischaemic and haemorrhagic, are attributable to a relatively small number of risk factors which are readily manageable in primary care setting. Implementation of best-practice recommendations for risk factor management is calculated to reduce stroke recurrence by around 80%. However, risk factor management in stroke survivors has generally been poor at primary care level. A model of care that supports long-term effective risk factor management is needed. Aim: To determine whether the model of Integrated Care for the Reduction of Recurrent Stroke (ICARUSS) will, through promotion of implementation of best-practice recommendations for risk factor management reduce the combined incidence of stroke, myocardial infarction and vascular death in patients with recent stroke or transient ischaemic attack (TIA) of the brain or eye. Design: A prospective, Australian, multicentre, randomized controlled trial. Setting: Academic stroke units in Melbourne, Perth and the John Hunter Hospital, New South Wales. Subjects: 1000 stroke survivors recruited as from March 2007 with a recent (<3 months) stroke (ischaemic or haemorrhagic) or a TIA (brain or eye). Randomization: Randomization and data collection are performed by means of a central computer generated telephone system (IVRS). Intervention: Exposure to the ICARUSS model of integrated care or usual care. Primary outcome: The composite of stroke, MI or death from any vascular cause, whichever occurs first. Secondary outcomes: Risk factor management in the community, depression, quality of life, disability and dementia. Statistical power: With 1000 patients followed up for a median of one-year, with a recurrence rate of 7–10% per year in patients exposed to usual care, the study will have at least 80% power to detect a significant reduction in primary end-points Conclusion: The ICARUSS study aims to recruit and follow up patients between 2007 and 2013 and demonstrate the effectiveness of exposure to the ICARUSS model in stroke survivors to reduce recurrent stroke or vascular events and promote the implementation of best practice risk factor management at primary care level.